Islamic Financial Development, Country Risk, and Human Development: Do They Shape Income Inequality in OIC Countries? - Hapid Durohman; Fajar Andrian Sutisna; Danial Muhammad Wirdyansyah (Muslim Business and Economics Review, 2025)
Income inequality remains a persistent development issue across member countries of the Organization of Islamic Cooperation (OIC), irrespective of their income level. The Islamic financial system, built upon Shariah principles of fairness, risk-sharing, and ethical finance, offers a viable alternative to conventional systems in addressing inequality. This study investigates the long-run effects of Islamic financial development, human development, and country risk on income inequality in OIC countries and empirically tests the Islamic Financial Kuznets Curve (IFKC) hypothesis. Using balanced panel data from 13 OIC member states over the period 2013–2023, the analysis applies Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) estimators using STATA17. The results confirm that Islamic financial development significantly reduces income inequality and follows a non-linear (inverted U-shaped) relationship, validating the IFKC hypothesis. Human development exhibits a mixed effect: while DOLS and non-linear models suggest an equalizing impact, FMOLS results indicate that early gains may benefit elite groups disproportionately, reflecting institutional asymmetries. Country risk consistently exacerbates inequality across all models. Moreover, interaction effects reveal that institutional quality moderates the relationship between human development, country risk, and inequality. In some cases, even stronger institutions may fail to ensure equity when they lack inclusivity. These findings highlight the importance of aligning Islamic financial expansion with inclusive governance and social development policies. For OIC policymakers, achieving sustainable and inclusive growth requires synergy between financial deepening, human development, and institutional transformation Keywords: Islamic financial development, Income inequality, Human development, Country risk, Islamic Financial Kuznets Curve